1999
DOI: 10.1093/nar/27.10.2165
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Ku70-binding proteins (KUBs)

Abstract: DNA-dependent protein kinase (DNA-PK) plays a critical role in resealing DNA double-stand breaks by non-homologous end joining. Aside from DNA-PK, XRCC4 and DNA ligase IV, other proteins which play a role(s) in this repair pathway remain unknown; DNA-PK contains a catalytic subunit (DNA-PKcs) and a DNA binding subunit (Ku70 and Ku80). We isolated Ku70-binding proteins (KUB1-KUB4) using yeast two-hybrid analyses. Sequence analyses revealed KUB1 to be apolipoprotein J (apoJ), also known as X-ray-inducible transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 47 publications
3
104
0
5
Order By: Relevance
“…XRCC6BP1 shows amplification frequencies similar to CDK4 within the 12q amplicon and is overexpressed in glioblastoma-derived cell lines and in primary glioblastoma (Fischer et al, 2001). Binding of XRCC6BP1 to Ku70 suggested a role of this protein in NHEJ (Yang et al, 1999). Our preliminary results on the function of XRCC6BP1 in glioblastoma cell lines are consistent with the idea that XRCC6BP1 is involved in DSB repair (data not published).…”
Section: Kub3 As Potential Modulator Of Dsb Repairsupporting
confidence: 87%
See 1 more Smart Citation
“…XRCC6BP1 shows amplification frequencies similar to CDK4 within the 12q amplicon and is overexpressed in glioblastoma-derived cell lines and in primary glioblastoma (Fischer et al, 2001). Binding of XRCC6BP1 to Ku70 suggested a role of this protein in NHEJ (Yang et al, 1999). Our preliminary results on the function of XRCC6BP1 in glioblastoma cell lines are consistent with the idea that XRCC6BP1 is involved in DSB repair (data not published).…”
Section: Kub3 As Potential Modulator Of Dsb Repairsupporting
confidence: 87%
“…A chromosome region on 12q is frequently amplified in glioblastoma and encompasses various genes crucial for the biology of this tumor including genes CDK4 and MDM2 (Reifenberger et al, 1996;Munnia et al, 2001). In addition, the amplified domain on chromosome 12q contains a gene encoding a Ku70-binding protein that was formerly termed KUB3 (Yang et al, 1999) and has been renamed XRCC6BP1. XRCC6BP1 shows amplification frequencies similar to CDK4 within the 12q amplicon and is overexpressed in glioblastoma-derived cell lines and in primary glioblastoma (Fischer et al, 2001).…”
Section: Kub3 As Potential Modulator Of Dsb Repairmentioning
confidence: 99%
“…16 Elucidation of the function of CLU in cells after stress is clearly complicated by the recognition of two different forms of the protein which apparently have two separate functions in the cell. A number of studies 1,5,13,16,17 have demonstrated that overexpression of the full-length CLU mRNA that would produce, depending on where the translation would start from and in this case, nCLU, acts as a prodeath signal, inhibiting cell growth and survival. However, other studies 2,6,8,10,[17][18][19] have shown that CLU expression may exert cytoprotective properties.…”
Section: Clu Apoptosis and Cell Cycle Regulationmentioning
confidence: 99%
“…8 High levels of nCLU were reported to cause G 1 cell cycle arrest in distinct cell types. 16 The overall function of CLU expression in cell cycle regulation remains unclear. Use of short interfering RNAs (siRNAs) specific to each form of the CLU proteins should allow future studies to delineate cause-effect relationships and reveal whether sCLU or nCLU directly affect cell cycle regulation with or without cell stress.…”
Section: Clu Apoptosis and Cell Cycle Regulationmentioning
confidence: 99%
See 1 more Smart Citation